The constructions of everyday ethics in Lithuanian family social work practices - Motieciene, Roberta; Laitinen, Merja; Skaffari, Pia (Socialinė teorija, empirija, politika ir praktika, 2019)
[straipsnis ir santrauka anglų kalba]